The Effect of Split Nerve on Electromyography Signal Pattern in a Rat Model - Deslivia, Maria Florencia; Lee, Hyun-Joo; Zulkarnain, Rizki Fajar; Zhu, Bin; Adikrishna, Arnold; Jeon, In-ho; Kim, Keehoon (Journal of Reconstructive Microsurgery, 2018)
Background Recent developments of prosthetic arm are based on the use of electromyography (EMG) signals. To provide improvements, such as coordinated movement of multiple joints and greater control intuitiveness, higher variability of EMG signals is needed. By splitting a nerve lengthwise, connecting each half to new target muscles, and employing a program to assign each biosignal pattern to a specific movement, we hope to enrich the number of biosignal sites on amputees' stump.Methods We split the gastrocnemius muscle of 12 Sprague-Dawley rats into two muscle heads, searched for the peroneal nerve, divided them lengthwise, and connected one half of the nerve to the tibial nerve innervating both muscle heads (SN_50, n = 8). In another group, we connected the undivided peroneal nerve to the nerve of a single muscle head (non-SN_100, n = 6), while the other muscle head received different innervation (non-SN_0, n = 6). After 10 weeks, we stimulated the peroneal nerve and measured the EMG amplitude.Results Mean EMG amplitude of the muscle head innervated by one half of the nerve (SN_50; 1.77 [range: 0.71–3.24] mV) and by the undivided nerve (non-SN_100; 3.45 mV [range: 1.13–5.34]) was not significantly different. However, the mean EMG amplitude produced by SN_50 was significantly different from that of the other innervation (i.e., non-SN_0; 0.76 mV [range: 0.41–1.35]), indicating the presence of noise.Conclusion Split nerve in combination with split-muscle procedure can yield a meaningful EMG signal that might be used to convey the intention of living organism to a machine.
Keywords: nerve transfer; myoelectric signals; prosthetic limb